2017
DOI: 10.1080/16549716.2017.1331579
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes towards mental health and the integration of mental health services into primary health care: a cross-sectional survey among health-care workers in Lvea Em District, Cambodia

Abstract: Background: Cambodia is a country where the resources for treating mental health disorders are far from sufficient. One strategy to narrow the treatment gap is to integrate mental health into primary health care (PHC). Understanding the knowledge and attitudes towards mental health integration that health-care workers have is important for assessing the challenges and opportunities when planning a potential integration project.Objective: The aim of this study was to assess these basic conditions in Lvea Em Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 32 publications
7
19
0
Order By: Relevance
“…More specifically, most PCPs in our sample did not answer the following questions favorably: (1) people with mental illness are dangerous more often than not; and (2) the public does not need to be protected from people with mental illness. This fear, an effect of stigmatization common in other low-resource settings [ 12 , 27 30 ], may help explain, in part, why most PCPs in our sample (91.8%) reported feeling very confident in their capability to refer patients to more specialized care, which, in Tunisia, is frequently remote from the homes and communities of patients [ 23 , 58 ]. Confidence in referral to specialized care also seems to be concretely translated into self-reported practice; per week, PCPs refer most people consulting for mental health issues to specialized resources (55.6; SD = 30.8; Q1 = 30.0, Q2 = 50.0, Q3 = 80.0).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, most PCPs in our sample did not answer the following questions favorably: (1) people with mental illness are dangerous more often than not; and (2) the public does not need to be protected from people with mental illness. This fear, an effect of stigmatization common in other low-resource settings [ 12 , 27 30 ], may help explain, in part, why most PCPs in our sample (91.8%) reported feeling very confident in their capability to refer patients to more specialized care, which, in Tunisia, is frequently remote from the homes and communities of patients [ 23 , 58 ]. Confidence in referral to specialized care also seems to be concretely translated into self-reported practice; per week, PCPs refer most people consulting for mental health issues to specialized resources (55.6; SD = 30.8; Q1 = 30.0, Q2 = 50.0, Q3 = 80.0).…”
Section: Discussionmentioning
confidence: 99%
“…These negative experiences within the healthcare system are attributable in part to healthcare professionals’ stigma against mental illness. For example, studies show how common it is for healthcare workers to believe that people with mental illness are “violent” and “dangerous” [ 12 , 27 30 ]. Studies also show that stigmatizing views against mental illness encourage healthcare professionals to associate mental illness with personal, moral faults or weakness [ 13 , 14 , 31 ] and describe people consulting for mental health conditions with derogatory terms, such as “crazy” and “mad” [ 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In India it was found that primary care doctors described integration programmes of mental health into PHC as valuable and that they became more involved in the integration due to observed benefits of patients’ clinical outcomes and positive feedback from the patients [ 37 ]. Interviews with health care workers in Lvea Em District also show support of the integration of mental health services into PHC and most of them were willing to personally deliver mental health care [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neimi et al identified low levels of knowledge of depression among health workers in northern Vietnam [ 30 ]. Low levels of knowledge about mental illness among PHPs has also been identified in other contexts, in both high-income [ 33 ] and low-income settings [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%